Online Exams: The Need for Best Practices and Overcoming Challenges - Margaret H. Williamson (Journal of Public and Professional Sociology)
An online educational environment differs from the traditional classroom in a number of ways. One thing that is consistent, though, is the need to protect the academic integrity of the course. In a face-to-face setting, faculty may be very familiar with how to do this, but in an online setting, there are certain steps that need to be taken to ensure the academic integrity of the course. One of the challenges in an online environment is the effectiveness of online exams and how to prevent cheating. This paper will discuss the need and importance of implementing best practices and some best practices associated with online exams.